Repetitive aggressive encounters generate a long-lasting internal state in Drosophila melanogaster males - Kim, Yong-Kyu; Saver, Mathias; Simon, Jasper; Kent, Clement F.; Shao, Lisha; 邵丽莎; Eddison, Mark; Agrawal, Pavan; Texada, Michael; Truman, James W.; Heberlein, Ulrike (Proceedings of the National Academy of Sciences - PNAS, 2018)
Multiple studies have investigated the mechanisms of aggressive behavior in Drosophila; however, little is known about the effects of chronic fighting experience. Here, we investigated if repeated fighting encounters would induce an internal state that could affect the expression of subsequent behavior. We trained wild-type males to become winners or losers by repeatedly pairing them with hypoaggressive or hyperaggressive opponents, respectively. As described previously, we observed that chronic losers tend to lose subsequent fights, while chronic winners tend to win them. Olfactory conditioning experiments showed that winning is perceived as rewarding, while losing is perceived as aversive. Moreover, the effect of chronic fighting experience generalized to other behaviors, such as gap-crossing and courtship. We propose that in response to repeatedly winning or losing aggressive encounters, male flies form an internal state that displays persistence and generalization; fight outcomes can also have positive or negative valence. Furthermore, we show that the activities of the PPL1-γ1pedc dopaminergic neuron and the MBON-γ1pedc>α/β mushroom body output neuron are required for aversion to an olfactory cue associated with losing fights.